A Skeletal Symmetry Index for Patient Derived Quantitative Quality Control in 99mTc-MDP Bone Scintigraphy (Bangladesh Journal of Nuclear Medicine, 2026)
Introduction: This study utilizes the Skeletal Symmetry Index (SSI) to quantify bilateral uptake uniformity of 99mTc-MDP bone scintigraphy images, aiming to compare calculated values with previously published reference limits to differentiate physiological variation. Method: Bone scintigraphy data of 35 adult patients were analyzed retrospectively across five anatomical regions: skull, humerus, rib, iliac crest, and femur. Bilateral asymmetry was quantified using the mentioned SSI formula. Standard statistical analysis was performed to analyze and correlate the regional count data. Results: High degrees of bilateral symmetry were observed across all skeletal sites. The calculated SSI values (median) ranged from 2.12% (skull) to 7.28% (humerus). Spearman’s correlation showed exceptionally strong symmetry. Most of the regions showed random count variation, but the regional count of ribs exhibited a statistically significant right-sided prevalence in the Wilcoxon signed-ranks test, likely due to hepatic activity. All measured indices remain well below the 10% clinical threshold for pathological asymmetry. Conclusion: SSI confirms high skeletal symmetry that is well below previously published limits and serves as a practical tool for routine image quality controlBangladesh J. Nuclear Med. 28(2): 251-256, July 2025